Education research - Understanding the factors involved in inpatient communication for orthopedic trainees. (December 2021) - Daniel, Drew; Avedian, Raffi; Johnson, Tyler; Michaud, John B.; Weimer-Elder, Barbette; Kline, Merisa; Nassar, Aussama K.
Abstract: Background: "Interpersonal and Communication Skills" (ICS) is a core competency set forth by the ACGME. No structured curriculum exists to train orthopedics residents in ICS. Methods: Twenty-four out of thirty-five orthopedics residents completed the survey (69%). The survey had the following domains: [1] Demographics, [2] Communication Needs/Goals, and [3] Communication Barriers. Results: Eighty-three percent of respondents wanted to improve their communication skills and their patient's experience. Interns-PGY4s wanted to improve on similar specific communication skills. All residents desired training in conflict management. Conclusion: There is a need among orthopedics residents for a communication skills curriculum early in residency training, specifically in conflict management. Highlights: In procedural training programs (including Orthopedics), there is less focus on non-technical skills acquisition. When surveyed, 83% of orthopedic trainees perceived a need to improve their communication skills. All orthopedic trainees wanted training in conflict management.